2021
DOI: 10.1055/s-0040-1719088
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos ligamentos acromioclavicular, coracoclaviculares e coracoclavicular medial na luxação acromioclavicular

Abstract: Resumo Objetivo Estudar a anatomia do ligamento coracoclavicular medial e avaliar a contribuição do ligamento acromioclavicular, coracoclaviculares e coracoclavicular medial na estabilidade da articulação acromioclavicular. Métodos Foram dissecados 26 ombros de 16 cadáveres frescos, posicionados em decúbito dorso-horizontal, com um coxim de 15 cm de altura entre as escápulas. Realizou-se uma via deltopeitoral estendida proximal e medialmente. Realizou-se dissecção por planos e identificação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…In this regard, the findings of this review support the notion that there are a variety of surgical techniques available for the surgical treatment of acromioclavicular displacement [1]. Because of the number of options and structures involved [26], each procedure retains its competencies, domains and problems [27] [28].…”
Section: Discussionsupporting
confidence: 58%
“…In this regard, the findings of this review support the notion that there are a variety of surgical techniques available for the surgical treatment of acromioclavicular displacement [1]. Because of the number of options and structures involved [26], each procedure retains its competencies, domains and problems [27] [28].…”
Section: Discussionsupporting
confidence: 58%
“…To date, dynamic AC joint distance has only been investigated by a few studies, which primarily focused on the AC distance or space with the arm relaxed. 8,16,19,37,44 Filho et al 8 dissected the AC joint capsule and measured the AC distance without active muscle contractions. Jensen et al 16 reported the average AC distance (4.9 mm) on the uninjured side of patients with AC joint reconstruction by ultrasound; however, only 1 frontal plane of the AC joint was used for measurements, by which the minimum distance between the acromion and the clavicle was unable to be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…11 CC ligament reconstruction is currently recommended for ACJ dislocation because the CC ligament plays a crucial role in the physiological function of the ACJ. 12,13 CC stabilization using Endobuttons placed either via open surgery or arthroscopically reportedly achieves good clinical and radiological outcomes. 14,15 However, the difficult part of the Endobutton technique for CC stabilization was placement of the Endobutton at the coracoid base, 16 which often required repeated attempts.…”
Section: Introductionmentioning
confidence: 94%
“…However, each surgical technique has advantages and disadvantages, and there is no consensus regarding the “gold standard” of fixation for acute Rockwood type III ACJ dislocation 11 . CC ligament reconstruction is currently recommended for ACJ dislocation because the CC ligament plays a crucial role in the physiological function of the ACJ 12,13 . CC stabilization using Endobuttons placed either via open surgery or arthroscopically reportedly achieves good clinical and radiological outcomes 14,15 .…”
Section: Introductionmentioning
confidence: 99%